Merits of Student- Centered Learning in Anatomy - Sawant, Sharadkumar Pralhad; Rizvi , Shaheen (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
This chapter focuses on merits of student- centered learning in anatomy. Anatomy plays a crucial role in several medical specialties. Anatomy holds significance not only in clinical practice but also in medical research and advancements. Research studies frequently rely on the analysis of anatomical structures to comprehend disease mechanisms, develop new treatments, and advance medical technology. Its role in research is vital for driving transformation and progress in the medical field. It is impossible to overstate the clinical importance of anatomy in undergraduate medical education. Because medical professionals examine and work with the human body on a daily basis, anatomy studies in one way or another will always be crucial to safe medical practice. It is necessary for core knowledge of anatomy to be assimilated by all doctors in order to practice medicine safely. It may be true that most doctors do not need to dissect a cadaver or study a prosection in order to practice, but if they do, it can improve their understanding and this surely has to be of benefit both for the safety of the patient and satisfaction of the doctor as a professional. Teacher-centered learning is different from student-centered learning in that the former refers to methods of instruction where students are allowed to take charge of learning activities, actively participate in class discussions, create their own learning projects, investigate subjects that pique their interest, and generally help to design their own coursework. In place of the prior lecture-based format, we should create and implement an instructional design that emphasizes the integration of student-centered pedagogy and active learning. Students' attitudes and performance will improve over time as a result of these adjustments. Although the changes to be implemented may require a significant time commitment in the first year, it will essentially be a “one time investment” because it will not require extra effort to teach the revised model in the future. Furthermore, it will not only provide a model for revision of an individual course but can also provide a catalyst for institutional reform.